Linking of oxidative stress and mitochondrial DNA damage to the pathophysiology of idiopathic intrauterine growth restriction - Apurva Singh; Jaiswar, Shyam Pyari; Apala Priyadarshini; Sujata Deo (International Journal of Health Sciences, 2023)
Objective: A common and serious pregnancy issue known as intrauterine growth restriction (IUGR) occurs when the fetus is unable to reach its full growth potential. Mitochondria are crucial to the development of the fetus and the placenta. We aimed to elucidate the role of oxidative stress parameters and markers of DNA damage. The integrity of the mitochondrial DNA (mtDNA) was studied. Methods: Blood samples were collected from 48 females (cases and controls, respectively). Oxidative stress parameters were analyzed. DNA was extracted followed by high-performance liquid chromatography to study 8-OH-dG and mtDNA by real time polymerase chain reaction. Western blot analysis was performed for nuclear encoded mitochondrial proteins and DNA damage markers. Results: When pregnant women were compared to non-pregnant women in their first, second, and third trimesters, a highly significant progressive drop in circulating mtDNA was found. In addition, mtDNA was considerably higher in mothers carrying IUGR fetuses than in healthy pregnancies. Sirtuin-3 protein expression was considerably suppressed in the IUGR placenta (P = 0.027), whereas Nrf1 expression was not statistically different from the control group in the IUGR. Increased oxidative stress led to greater DNA damage in IUGR. The highest concentrations of 8-OH-dG were found in IUGR with levels significantly higher than those in the non-pregnant group. Conclusion: Our research sets the path for further investigation into mitochondrial anomalies in IUGR pregnancies and offers evidence for disturbed mitochondrial homeostasis. The mtDNA might offer a fresh perspective on the processes involved in physiological gestation. In addition, the presence of mtDNA may aid in the diagnosis of IUGR during pregnancy.